PENGARUH INVESTASI ASING LANGSUNG TIONGKOK TERHADAP DOMINASI TIONGKOK DI ZAMBIA - Andri Laksamana; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This paper describes the investment of Chinese direct foreign investment in Zambia toward China's domination in Zambia. Zambia as a developing country is a destination for Chinese investment abroad. China invests more in Zambia in various sectors of Zambia's economy.This research uses the perspective of liberalism as a reference to analyze China's domination in Zambia through Chinese investment in Zambia. This research uses the theory of foreign investment to see the economic and political advantages of imports through investment. This research also use Sphere Influence concept to analyze china influence in Zambia.The result of this research is that Chinese investment in Zambia is increasing China's use in Zambia. With increased investment in various sectors of the Zambian economy and the China-Zambia Special Economic Cooperation Zone can improve China's economy and politics in Zambia. China uses investment as a step to expand domination abroad. China can control Zambia's natural resources, expand industrial estates and send workers from Zambia and improve bilateral relations between China and Zambia.Keywords: Investment, company, special economic zone, interests, political economy.